Blue Carbon Potential of Salt Marshes in Kulon Progo for Climate Change Mitigation in Indonesia: english - Mustofa, Ikrom; Wacano, Dhandhun; Setyawan, Bagus Dwi; Faradis, Irsyad; Nabil, Hilbram; Khaidar, Muhammad Al; Minnen, Tjalf van (UII, 2025)
Salt marshes along the coast of Kulon Progo in Yogyakarta can act as blue carbon storage facilities to achieve the climate change mitigation goals outlined in Indonesia’s Nationally Determined Contributions (NDC) for 2030. Three villages in Temon District became the location of this research: Glagah, Palihan, and Jangkaran Villages. A mixed-methods approach was employed in this research, encompassing direct field observation, soil and vegetation analysis in their capacity as carbon storage, and interviews with individuals in the 3 villages. The results of the analysis showed that there was a small amount of carbon content in various locations in the 3 villages. Mangroves and pine trees, particularly those growing around swamps, play a significant role in carbon absorption. However, this study revealed a decrease in the potential of salt marsh land due to changes in land use to Yogyakarta International Airport (YIA) and the surrounding city planning. As a result, carbon storage capacity is reduced, and carbon emissions from land that has changed function are higher. The study also sees the importance of strengthening government policies and regulations and increasing community participation in salt marsh conservation through village-based programs such as the Climate Village Program (PROKLIM) and Resilient Coastal Village. The study concludes that through salt marsh conservation, the potential for blue carbon becomes more significant, which also requires collaboration between stakeholders.